Spatiotemporal parameters and kinematics differ between race stages in trail running—a field study - Genitrini, Matteo; Fritz, Julian; Stöggl, Thomas; Schwameder, Hermann (Frontiers in Sports and Active Living, 2024)
Introduction Trail running is an emerging discipline with relatively few studies performed in ecological conditions. The aim of this work was to investigate if and how spatiotemporal parameters (STP) and kinematics differ between initial and final stage of a field trial. Methods Twenty trail runners (10 F, 10 M) were recruited and ran a solo 9.1 km trial. During the test, participants wore a GPS watch and an IMU-based motion capture system. Running speed, elapsed time, STP and kinematics were compared between initial and final stage, separately for uphill (UH) and downhill (DH) sections. Results Running speed decreased in the final stage (p<0.05). Total test time was more correlated to the time elapsed in UH sections. In the final stage and in both UH and DH sections, contact time and duty factor increased, whilst stride length and flight time decreased (p<0.05). In the final stage, ankle joint was more dorsiflexed in stance and swing phases in UH sections and stance phase only in DH sections (p<0.05). In the final stage, knee joint was less extended in swing phase in UH and DH sections, as well as less extended in stance in UH sections (p<0.05). In the final stage, hip joint was less flexed in the swing phase in UH and DH sections (p<0.05). In the final stage, forward trunk lean was higher across the entire gait cycle in in UH sections (p<0.05). Trunk contralateral axial rotation was lower, in DH sections (p<0.05). Discussion During the final stage, results indicate a less efficient propulsion phase, in both UH and DH sections. In UH sections, results suggest lower energy generation at the ankle joint. In DH sections, results suggest that the kinematics of swing leg may play a role in sub-optimizing propulsion phase. This study demonstrates how, in UH and DH sections, similar changes in spatiotemporal parameters can be elicited by dissimilar changes in running kinematics. To optimize performance in trail running, coaches and practitioners are advised to work on different (incline-specific) aspects of running technique.